An overview of the circular economy among SMEs in the Basque country: A multiple case study - Marta Ormazabal; Vanessa Prieto-Sandoval; Carmen Jaca; Javier Santos (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: This research analyzes the maturity of environmental management as well as the degree of to which the Circular Economy has been implemented in Basque SMEs. Design/methodology/approach: A total of 17 case studies were carried out in industrial SMEs companies in the Basque Country. Findings: The main results show that companies are limited to complying with the law and in many cases are worried about the image of the company, although they are not committed to environmental issues. There is still a lot to do in SMEs, as they are the companies that face the biggest challenges due to a lack of resources. Originality/value: Circular Economy aims to change a linear economy into promoting sustainability of the economy while also engaging in sustainable environmental protection. This research has focused on small and medium enterprises as they represent a 99% of companies in Europe and they are the ones that have the most difficulty reaching a stage of environmental excellence due to their limited resources.
Keywords: 650; circular economy; basque industry; industrial ecology